Postfeminism and organization
1 online resource
Keywords: This edited book inserts postfeminism (PF) as a critical concept into understandings of work and organization. While the notion of PF has been extensively investigated in cultural and media studies, it has yet to emerge within organization studies - remaining marginal to understandings of work based experiences and subjectivities. Understanding PF as a discursive cultural context not only draws on an established epistemological orientation to organizations as discursively constructed and reproduced but allows us to highlight how PF may underpin and be underpinned by other discursive regimes This book, as the first in the field, draws on key international authors to explore: the contextual backdrop' of PF and its links with neo-liberalism, transnational feminism and other hegemonic discourses; the different ways in which this backdrop has infiltrated organizational values and practice through the primacy attached to choice, merit and individual agency as well as through the widespread perception that gender disadvantage has been solved'; and the implications for organizational subjectivity and for how inequality is experienced and perceived. This book introduces postfeminism as a critical concept with contemporary importance for the study of organizations, arguing for its explanatory potential when: Exploring women's and men's experience of managing and organizing; Investigating the gendered aspects of organizational life; Analysing the contemporary validation of the feminine and the associated feminization of management/leadership and organizations; Tracing the emergence of new femininities and masculinities within organizational contexts. The book is ideal reading for researchers working in the area of Gender and Organization Studies but is also of interest to researchers in the areas of Cultural Studies, Media Studies, Women's Studies and Sociology.